Food Intake and Core Body Temperature of Pups and Adults in a db Mouse Line Deficient in the Long Form of the Leptin Receptor without Misty Mutation - Wijang Pralampita Pulong; Miharu Ushikai; Emi Arimura; Masaharu Abe; Hiroaki Kawaguchi; Masahisa Horiuchi (Journal of Diabetes Research)
Different involvement of leptin signaling in food intake (FI) and body temperature (BT) in pups and adults has been suggested. However, the leptin receptor (Lepr) long-form-deficient (db) mouse line has not been fully examined in pups. In the most available db mouse line, wild-type (WT) mice have a mutation in the dedicator of cytokinesis 7 gene, named misty, which was recently revealed to be involved in neuronal development. Therefore, we established a line of db mice without the misty mutation using natural mating. Adult (8 weeks of age) homozygous db/db mice displayed significantly higher core body weight (BW) and FI and significantly lower core BT than WT mice. However, postnatal (2 weeks of age) db/db mice displayed similar BW and milk intake and significantly lower core BT than WT mice. Correspondingly, adult and postnatal db/db mice exhibited altered mRNA levels of hypothalamic orexigenic and anorexigenic peptide in adults but not in pups. Additionally, db/db mice displayed significantly lower mRNA levels of brown adipose tissue uncoupling protein 1 at both ages. In conclusion, the db mouse line without the misty mutation clearly showed the different involvements of the Lepr long form in FI and BT in pups and adults.